STUDY THE EFFECT OF FRONT SPEED AND WORKING WIDTH ON SOME PERFORMANCE INDICATORS, POWER REQUIREMENT AND ECONOMIC COSTS FOR DIFFERENT SIZES OF AGRICULTURAL TRACTORS - & Jarad, Tahir (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This research was conducted to study the exploitation of speed and working width for different tractors with best performance rate and lower costs, and study of the efficiency and amount disbursed energy. The research was conducted in the Dibs region in Kirkuk governorate in September 2015, in two different locations of the soil texture, Randomized complete block design by split split plot system with three replications and Duncan test were used to compare the means of treatment at 5%. The results showed the best quadrate interaction which achieved the best technical results, economically and indicators of the power indicators in speed (6.24Km / h) and working width (120cm) with three tractors in the first location where it was found that the tractor size (82KW) have achieved higher value of effective field capacity of (0.529 ha / h) and less fuel consumption at a rate (14.37L / ha) and the soil distribution volume was (1052m3 / ha) and with the least specific resistance (55.41kN / m2) and with highest efficiency to exploit and the amount of spent energy of ( 18.04mj / ha) with less energy requirements (32.05KW.h / ha) and highest the specific energy efficiency (SEE) (76.87%) and lowest value of amount of spent energy (599mj / ha), followed by the tractor (67KW) and then tractor (56KW), while outperformed tractor (56 KW) superiority recorded the highest power delivery efficiency at a rate of (34.64%) and lower costs of plowing (40642 ID / ha), followed by the tractor (67kw) while registered tractor (82KW) less the value of the power delivery efficiency at a rate of (24.68%) and the highest costs to the process of plowing at a rate (75.295ID / ha), apparently through these results that the tractor (82KW) is the best productive and technically taking into account the size of the agricultural lands and irrigation method to complete the work on time has been shown through the study of productivity and the technical and economic specifications possibility of reaching a better productivity and better performance at the lowest costs.